Targeted costing technology as an integrated framework for rationalizing international marketing decisions: A study of implementing a partnership between the General Company for Leather Industries and a foreign producer and marketer. - أسماء رشيد علي (Iraqi Journal for Administrative Sciences, 2024)
This research’s subject is concedered a basic problem , which recently became , of the most serouse barrier in the Iraqi markets , especially for local products . As for the greatness of the competitions of imported goods , and for it’s diversity , plentiful . Thus Marketing of the Iraqi products turned to be a problem for each producer , in both government and privet sectors . The research contains four sections , The first section of this research is about the research’s methodology. The research shows the theoretical form for Target costing , as an essential axis in the theoretical part of the research , in the second section , as well as a brief introduction of marketing and international marketing . The third section , represents the practical part of the research , which shows the estimated cost details (targeted) , that is expected to incurred by the company (The research subject) , that had been restrict , as to be limited by the target price , the product will be soled by , at the out side markets , by the investor and marketer (the partner) . As for the forth section . It contains the conclusions and the recommendations , the researcher inferred from this research .